If <em>x</em> + 1, <em>x</em> - 5, and <em>x</em> - 2 are in a geometric progression, then there is some constant <em>r</em> for which
<em>x</em> - 5 = <em>r</em> (<em>x</em> + 1)
==> <em>r</em> = (<em>x</em> - 5) / (<em>x</em> + 1)
and
<em>x</em> - 2 = <em>r</em> (<em>x</em> - 5)
==> <em>r</em> = (<em>x</em> - 2) / (<em>x</em> - 5)
Then
(<em>x</em> - 5) / (<em>x</em> + 1) = (<em>x</em> - 2) / (<em>x</em> - 5)
Solve for <em>x</em> :
(<em>x</em> - 5)² = (<em>x</em> - 2) (<em>x</em> + 1)
<em>x</em> ² - 10<em>x</em> + 25 = <em>x</em> ² - <em>x</em> - 2
-9<em>x</em> = -27
<em>x</em> = 3
It follows that the ratio between terms is
<em>r</em> = (3 - 5) / (3 + 1) = -2/4 = -1/2
Now, assuming <em>x</em> + 1 = 4 is the first term of the G.P., the <em>n</em>-th term <em>a(n)</em> is given by
<em>a(n)</em> = 4 (-1/2)ⁿ⁻¹
The sum of the first 12 terms - denoted here by <em>S</em> - is then
<em>S</em> = 4 (-1/2)⁰ + 4 (-1/2)¹ + 4 (-1/2)² + … + 4 (-1/2)¹¹
Solve for <em>S</em> :
<em>S</em> = 4 [(-1/2)⁰ + (-1/2)¹ + (-1/2)² + … + (-1/2)¹¹]
(-1/2) <em>S</em> = 4 [(-1/2)¹ + (-1/2)² + (-1/2)³ + … + (-1/2)¹²]
==> <em>S</em> - (-1/2) <em>S</em> = 4 [(-1/2)⁰ - (-1/2)¹²]
==> 3/2 <em>S</em> = 4 (1 - 1/4096)
==> <em>S</em> = 8/3 (1 - 1/4096)
==> <em>S</em> = 1365/512